CORRELATING PRIMARY DYSMENORRHEA WITH ITS STRESSORS: A CROSS SECTIONAL STUDY INVESTIGATING THE MOST LIKELY FACTORS OF PRIMARY DYSMENORRHEA AND ITS EFFECTS ON QUALITY OF LIFE AND GENERAL WELL BEING - Komal Atta; Shireen Jawed; Sadaf Zia (Journal of University Medical & Dental College, 1970)
ABSTRACT Background: Dysmenorrhea is a frequent gynecological condition associated with painful cramping of uterine origin. Pain of severe dysmenorrhea is associated with restriction of activity and absence from the workplace. The causative stressors and impact of dysmenorrhea on quality of life have been enunciated rarely in a Pakistani setup. Objectives: To study relationship of primary dysmenorrhea with its stressors (family history, PMS, stress and physical activity) and to investigate the effect on Quality of Life (classabsenteeism, sleep and general wellbeing) of female university students. Methods: a cross study, data was collected from 250 students aged 16-23 of which 200 students were included after applying inclusion/ criteria (64 medical, 68 dental, 59 nutrition and 62 physical therapy students). The data was collected regarding age of menarche, presence or absence of dysmenorrhea, PMS, physical activity quality life and dietary habits by a structured questionnaire. Results: Dysmenorrhea was present in 86.5% of the girls. Majority reported PMS symptoms of cramping (32.7%), abdominal pain (44.7%), mood swings (40%). The major stressors for dysmenorrhea were stress (81.8%, p=0.018), followed by low physical activity(p=0.01). effects on quality of life due to dysmenorrhea included insomnia (51.8%, p=0.01),86.3% girls suffering from dysmenorrhea complained of difficulty concentrating in class and 39% of girls an odds ratio of greater than 1 in population experiencing dysmenorrhea to skip classes (p=0.005) and 64% of the girls described the pain to be interfering with daily activites(p=0.01) Conclusion: Lack of physical activity and stress are important causes of dysmenorrhea, which lead to adverse effects on quality of life on university students such as decrease concentration span, insomnia and class absenteei Ethical Considerations: Consent was taken from the students prior to giving them the questionnaires. Complete anonymity was assured. Permission to carry out the research was taken from the Dean of Allied Health Sciences, University of Faisalabad and the respective heads of departments. The study was approved by the Ethics Review Board of The University of Faisalabad.